Tamizdat as Masquerade: The Case of Aleksandr Solzhenitsyn’s Four Gulags - Yacobson, Alexander (Wiener Slawistischer Almanach, 2021)
This article investigates the early publication history of Aleksandr Solzhenitsyn’s Arkhipelag Gulag in order to develop a new understanding of Russian-language tamizdat. After exploring four separate yet textually identical versions of this book, it shifts to a broader discussion of tamizdat, arguing that the phenomenon is best understood not by looking for certain texts, but rather for a certain type of book. It concludes by detailing the specific book form employed by tamizdat, a type of book meant to hide illicit texts from the Soviet authorities.